Factors affecting foreign direct investment (FDI) inflows in Hanoi - Trần, Hồng Hoàng Nam (2020)
Study theoretical framework of FDI and influencing factors; Identify influencing factors FDI inflows in Vietnam (informal charges, training and labor policies, policy bias, legal institutions) and determinants of FDI inflows in Hanoi (informal charges, training and labor policies, policy bias) in a 5-year period from 2014 – 2018 based on analysis on PCI. Propose policy suggestions to increase FDI attraction for Hanoi in the coming time. Boosting trade openness by conducting promotion schemes Improvement of law system Improvement of human resources